Mode of delivery and maternal sexual wellbeing: A longitudinal study. (3rd August 2022) - Martin, Florence Z.; Madley‐Dowd, Paul; Ahlqvist, Viktor H.; Jónsson‐Bachmann, Egill; Fraser, Abigail; Forbes, Harriet
Abstract: Objectives: To investigate the association between mode of delivery and subsequent maternal sexual wellbeing. Design: Prospective birth cohort study. Setting: Avon (in Bristol area), UK. Population: Participants in the Avon Longitudinal Study of Parents and Children (ALSPAC). Methods: Mode of delivery was abstracted from obstetric records and sexual wellbeing measures were collected via a self‐report questionnaire. Missing data were imputed using multiple imputation, and ordinal logistic regression models for ordered categorical outcomes were adjusted for the covariates maternal age at delivery, pre‐pregnancy body mass index, diabetes during pregnancy, socio‐economic position, parity, depression and anxiety. Main outcome measures: Sexual enjoyment and frequency at four time points postpartum (between 33 months and 18 years) and two types of sex‐related pain (pain in the vagina during sex and elsewhere after sex) at 11 years postpartum. Results: We found no association between mode of delivery and sexual enjoyment (e.g. adjusted odds ratio [OR] 1.11, 95% confidence interval [95% CI] 0.97–1.27 at 33 months) or sexual frequency (OR 0.99, 95% CI 0.88–1.12 at 33 months). Caesarean section was associated with an increased odds of pain in the vagina during sex at 11 years postpartum as compared with vaginal delivery in the adjusted model (OR 1.74, 95% CI 1.46–2.08). Conclusions: These findings provide no evidence supporting associations between caesarean section and sexual enjoyment or frequency. However, mode of delivery was shown to be associated with dyspareunia, which may not be limited to abdominal scarring.